Implementasi Analythical Hierarchy Process pada Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi - Muhamad Yusuf Ismail; Lilis Dwi Farida (STMIK Banjarbaru, 2023)
The selection of outstanding students at a school is one of the routine activities. The selection aims to appreciate the seriousness of students in studying and screen out superior students for competitions. In determining outstanding students, the school uses Ms. Excel with different understanding of users. So that it can cause errors in the determination. In addition, uncertain assessment parameters can lead to high subjectivity. To assist schools in determining outstanding students, it is necessary to provide alternative decisions through a Decision Support System (DSS). The Analytical Hierarchy Process (AHP) method was chosen because human judgment can be translated into a calculation. In the AHP method there is also a Consistency Ratio which is useful for measuring the consistency value of the assessment weight. According to school requirements. SPK is built based on a website using PHP language and MySQL database. Based on system testing by the school, outstanding students can be determined through the SPK with suggestions in the form of alternative students with the highest total grades.Keywords: Decision Support System; Analytical Hierarchy Process; Best Student AbstrakPemilihan siswa berprestasi pada sebuah sekolah menjadi salah satu aktivitas rutin. Pemilihan tersebut bertujuan untuk mengapresiasi kesungguhan siswa dalam menuntut ilmu dan menyaring siswa unggul untuk lomba. Dalam menentukan siswa berprestasi, pihak sekolah memanfaatkan aplikasi Microsoft Excel dengan pemahaman pengguna yang berbeda-beda, sehingga hal tersebut dapat menyebabkan kesalahan dalam penentuan. Selain itu, parameter penilaian yang belum pasti dapat menimbulkan subjektifitas yang cukup tinggi. Untuk membantu sekolah dalam menentukan siswa berprestasi, perlu diberikan alternatif keputusan melalui Sistem Pendukung Keputusan (SPK). Metode Analytical Hierarchy Process (AHP) dipilih karena penilaian manusia dapat diterjemahkan ke dalam sebuah perhitungan. Dalam metode AHP juga terdapat Rasio Konsistensi yang berguna untuk mengukur nilai konsistensi bobot penilaian. Sesuai kebutuhan sekolah. SPK dibangun berbasis website dengan bahasa PHP dan database MySQL. Berdasarkan pengujian sistem oleh pihak sekolah, siswa berprestasi dapat ditentukan melalui SPK dengan saran berupa alternatif siswa dengan total nilai terbesar.Kata kunci: Sistem Pendukung Keputusan; Analytical Hierarchy Process; Siswa Berprestasi.